Teacher Educator's Professional Development - Javornik Krečič, Marija; Konečnik Kotnik, Eva (Journal for Geography, 2014)
This study examines the stages of teacher educators’ professional development. In a framework based on the literature on teacher professional development, we focus especially on the stages/levels of teacher educators’ professional development. The Results of an empirical study conducted at the University of Maribor in February 2012 indicate that there are no differences between the stages of professional development of teacher educators and non-teacher educators.
Keywords: non-teacher and teacher educators; stages of professional development